Pengaruh job embeddedness terhadap turnover intention (FENOMENA, 2021)
The objective of this study was to determine the direct effects of job embeddedness on turnover intention. The sample used was 253 Generation Y employees in Indonesia with working period of more than 9 months. The sampling technique used in this study was non-probability sampling. This study uses a Turnover Intention Scale (TIS-6) developed by Roodt (2004) with a reliability of 0,076 and Job Embeddedness Scale developed by Mitchel, et. al (2001) with reliability of 0,867. Data analysis uses Partial Least Square method with the help of Smart-PLS 3.0. software. The results of this study indicate that job embeddedness has a negative and significant direct effect on turnover intention.